Sejarah Markas Tentara Pelajar Sebagai Pusat Pertahanan di Kampung Akad Kenagarian Kambang Utara (1947-1949) - Suryadi Fajri; Vivi Juniati; Nurhameli Nurhameli; Defia Putri Renaldi; Witri Annisa (Tarikhuna: Journal of History and History Education, 2024)
The background of this research is that the valuable historical relics, namely the Central Sumatra Pesisir Selatan-Kerinci Student Army Headquarters, are located in the North Kambang area of Kampung Akad village. This is indicated by the fact that many general public do not know about the Student Army Headquarters. The purpose of this study was to find out how the History of the Students Army Headquarters as a Defense Center in the Akag Kenagarian North Kambang Utara Village. The research method was a historical research method, consisting of research steps, namely: first heuristic, the writer trying to collect data, second, source criticism, namely criticizing data from in terms of internal and external. The third interpretation is to provide an interpretation of the source or the fourth is historiography using data and facts that have been obtained. Research results (1) History of Standing Army Student Headquarters in Akad Village. In 1947, the Headquarters building was built based on community agreement to establish a health center in 1942 then in 1947 to coincide with the establishment of the Student Army so that this building was used as the Student Army Headquarters in this region. This building also functioned as a printing press for Oeang Republik Indonesia (ORI) Lengayang. (2) Activities carried out by the Student Army in Akad Village. Student Army activities are like doing mental training, such as students being told to enter the forest and out of the forest, training how to use Talang Bambu weapons